“The lands…belonged to them, once by the Indian title, twice for having defended them…and thrice for having built and lived on them”: The Law and Politics of Métis Title - Drake, Karen; Gaudry, Adam (Osgoode Hall Law Journal, 2016)
To predict what is on the horizon of the Métis legal landscape, we can look to jurisprudence on First Nations’ rights, given that Métis rights cases are typically ten to fifteen years behind those of First Nations. With the release of the Supreme Court of Canada’s decision in Tsilhqot’in, the next big issue in Métis law may be Métis title. Scholars have doubted the ability of Métis to establish Aboriginal title in Canada for two reasons: first, Métis were too mobile, and second, Métis were too immobile. This paper critically analyzes these positions and argues that the case for Métis title in Canada is a strong one. As such, governments in Canada would do well to focus on resolving outstanding Métis title claims.